Kinetics of CO2–fluid–rock reactions in a basalt aquifer, Soda Springs, Idaho. (October 2015) - Maskell, Alexandra; Kampman, Niko; Chapman, Hazel; Condon, Daniel J.; Bickle, Mike
Highlights: We model reaction progress in a basalt aquifer by using changes in groundwater. We use U-series isotope ratios to determine the surface area of plagioclase. Calculated dissolution rates for plagioclase compare to other CO2 -charged systems. Abstract: The dissolution of silicate minerals by CO2 -rich fluids and the subsequent precipitation of CO2 as carbonate minerals represent a means of permanently storing anthropogenic CO2 waste products in a solid and secure form. Modelling the progression of these reactions is hindered by our poor understanding of the rates of mineral dissolution–precipitation reactions and mineral surface properties in natural systems. This study evaluates the chemical evolution of groundwater flowing through a basalt aquifer, which forms part of the leaking CO2 -charged system of the Blackfoot Volcanic Field in south-eastern Idaho, USA. Reaction progress is modelled using changes in groundwater chemistry by inverse mass balance techniques. The CO2 -promoted fluid–mineral reactions include the dissolution of primary plagioclase, orthoclase, pyroxene and gypsum which is balanced by the precipitation of secondary albite, calcite, zeolite, kaolinite and silica. Mineral mole transfers and groundwater flow rates estimated from hydraulic head data are used to determine the kinetics of plagioclase and orthoclase feldspar dissolution. Plagioclase surface area measurements were determined using the evolution of the U-series isotope ratios in the groundwater and are compared to published surface area measurements. Calculated rates of dissolution for plagioclase range from 2.4 × 10 −12 to 4.6 × 10 −16 mol/m 2 /s and orthoclase from 2.0 × 10 −13 to 6.8 × 10 −16 mol/m 2 /s respectively. These feldspar reaction rates, correlate with the degree of mineral–fluid disequilibrium and are similar to the dissolution rates for these mineral measured in other natural CO2 -charged groundwater systems.